Development of the Test Instrument for Measuring Students' Critical Thinking Abilities on Fluid Material - Ni Nyoman Sri Putu Verawati; Saiful Prayogi; Muhammad Yusril Yusup; Hafsah Taha (IKIP Mataram, 2020)
This study aimed to develop a test instrument to measure students' critical thinking skills on fluid material. Characteristics of the instrument and its validity estimation are also described. This research and development study employed five stages of research, namely information collecting (literature review and preparation of the subject matter), planning (defining and formulating objectives), developing preliminary form of the test instrument, preliminary field testing (expert validation), and main product revision (in accordance with the recommendations in the preliminary field testing). The content and construct validity were estimated by expert validation. Results of the instrument validation showed average scores for each component (content validity index of 4.63 and construct validity of 4.75), both of which are in the very valid category. The final result of the instrument validation is 4.69 (very valid if: Va > 4.21), with 98.7% reliability. Description of the study result is presented further in this article.